The Role of Youth in Promoting Environmental Awareness in Barru Regency - Yusuf, Muh; Kadir, Abdul; Riswan, Riswan (Journal Social Civilecial, 2024)
The research aims to understand how young people in Barru Regency Indonesia support environmental consciousness through qualitative methods. The research investigates youth-led environmental initiatives by conducting in-depth interviews with participants alongside conducting focus groups and performing participant observation. Youth residents of Barru take part in different environmental advocacy practices which include waste disposal management and public awareness campaigns together with tree plantation activities. Youth leaders implement local knowledge and community-based methods to combat environmental problems while building their strategies from the ground up. Youth in their efforts encounter multiple obstacles including minimal resources together with insufficient backing from local officials and reluctance from older members of the population. Although faced by numerous barriers their community work successfully promotes environmental understanding alongside behavior alteration within the community. The study demonstrates how young people's environmental activism plays a vital role but requires expanded backing from authorities and community members to maintain such actions. The findings from this research add important knowledge about the effectiveness of youth environmental activism in rural areas of Indonesia through their contributions to scholarly literature.